(untitled) (Archaeologia Adriatica, 2018)
The following article presents the results of the study of one part of the archaeological material found during the excavations of the villa rustica in Caska on the island of Pag. The investigations were conducted in 2005 and 2006 by the company Geoarheo d.o.o. from Sesvete. Two square underground storage rooms and earthenware jars (dolia), reused as rubbish dumps, contained a big quantity of ceramic vessels. Among them, the Italian terra sigillata stands out, imported during the Augustan age mainly from the northern Italian area (Po Valley), but also from central Italy. Of particular significance are the bottoms of plates and cups bearing the potters’ stamps, important in the attempt of reconstructing the trade routes in Antiquity. The graffiti engraved on several vessels could be interpreted as the first two or three letters of the names of slaves or freedmen of Greek origin, laboring for a big land owner. The epigraphic monuments found in Caska bay suggest that the land property with the villa rustica was owned by one branch of the senatorial family of the Calpurnii Pisones.